The evolutionary biology of endometriosis. Issue 1 (12th March 2021) - Dinsdale, Natalie; Nepomnaschy, Pablo; Crespi, Bernard
Abstract: We provide the first analysis and synthesis of the evolutionary and mechanistic bases for risk of endometriosis in humans, structured around Niko Tinbergen's four questions about phenotypes: phylogenetic history, development, mechanism and adaptive significance. Endometriosis, which is characterized by the proliferation of endometrial tissue outside of the uterus, has its phylogenetic roots in the evolution of three causally linked traits: (1) highly invasive placentation, (2) spontaneous rather than implantation-driven endometrial decidualization and (3) frequent extensive estrogen-driven endometrial proliferation and inflammation, followed by heavy menstrual bleeding. Endometriosis is potentiated by these traits and appears to be driven, proximately, by relatively low levels of prenatal and postnatal testosterone. Testosterone affects the developing hypothalamic–pituitary–ovarian (HPO) axis, and at low levels, it can result in an altered trajectory of reproductive and physiological phenotypes that in extreme cases can mediate the symptoms of endometriosis. Polycystic ovary syndrome, by contrast, is known from previous work to be caused primarily by high prenatal and postnatal testosterone, and it demonstrates a set of phenotypes opposite to those found in endometriosis. The hypothesis that endometriosis risk is driven by low prenatal testosterone, and involves extreme expression of some reproductive phenotypes, is supported by a suite of evidence from genetics, development, endocrinology, morphology and life history. The hypothesis also provides insights into why these two diametric, fitness-reducing disorders are maintained at such high frequencies in human populations. Finally, the hypotheses described and evaluated here lead to numerous testable predictions and have direct implications for the treatment and study of endometriosis. Lay summary: Endometriosis is caused by endometrial tissue outside of the uterus. We explain why and how humans are vulnerable to this disease, and new perspectives on understanding and treating it. Endometriosis shows evidence of being caused in part by relatively low testosterone during fetal development, that 'programs' female reproductive development. By contrast, polycystic ovary syndrome is associated with relatively high testosterone in prenatal development. These two disorders can thus be seen as 'opposite' to one another in their major causes and correlates. Important new insights regarding diagnosis, study and treatment of endometriosis follow from these considerations.